A comparative study of self-centering precast concrete walls with replaceable buckling-restrained yielding plates or friction dissipation components. (1st April 2023) - Li, Xinghua; Kurama, Yahya C.; Wu, Gang; Cui, Haoran; Tang, Yuchuan; Zeng, Yihua
Highlights: Self-centering walls with buckling-restrained plates were compared with that with friction plates. Both wall systems showed excellent self-centering, energy dissipation up to more than 3.5% drift. Frictional energy dissipation is greater and more stable than yielding dissipation. Wall with friction plates can further work without repair after a major earthquake. Effects of losses in the friction bolt force and PT force were investigated. Abstract: Two new unbonded post-tensioned (PT) self-centering precast concrete wall systems with excellent reparability and seismic resilience are investigated in this paper through cyclic loading testing of four large-scale precast walls. As major innovative features, reparability and seismic resilience of the structures are achieved by using externally connected replaceable buckling-restrained yielding plates (Type I) or friction components (Type II), and steel jackets to confine concrete at wall toes. Both types of wall specimens showed excellent self-centering, energy dissipation, and ductile behavior over 3.5–4% lateral drift without significant strength reduction, demonstrating remarkable advantages over monolithic cast-in-place (CIP) walls and self-centering precast concrete walls with yielding reinforcing bars. The damage in the proposed walls concentrated in the external energy dissipation components, with minor concrete cracking and no concrete crushing at the completion of testing, making repairs feasible by replacing the damaged components. The energy dissipating capacity for the Type II wall was significantly greater than those for the Type I walls at relatively small drift levels due to the large initial stiffness of friction-based damping. As there was no significant damage in the friction damping components throughout testing, the energy dissipation for the Type II wall was much more stable than those for the Type I walls. Comprehensive finite element models were also developed for both types of walls, which satisfactorily captured the global and local behaviors, including prediction of minor concrete damage, steel and concrete strains, and nonlinear behavior of the energy dissipation components. A parameter study was subsequently conducted to investigate the effects of losses in the friction bolt force and PT force on the wall behavior. Overall, both types of walls can be used in the life-line structures that have great demand for fast reparation and restoration of their original lateral resistance and energy dissipation after a major earthquake.